PENGARUH KEBIJAKAN MANAJEMEN KEUANGAN TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTY - Silvia, Dewi; Sari, Meita Sekar; Salma, Nur; Sari, Elina Mutia (Universitas Muhammadiyah Palembang, 2022)
Policy Funding decisions can be interpreted as decisions concerning the company's financial structure (financial structure). Dividend policy is the distribution of operating results or profits given to shareholders. This study aims to determine whether funding decisions and dividend policy have a simultaneous effect on firm value in the property sector listed on the Indonesia Stock Exchange. The type of data source used in this study is secondary data. librarians. The sampling procedure in this study was non-probability with purposive sampling technique. The method of analysis uses the classical assumption test, multiple linear regression analysis, hypothesis testing, Determinant Coefficient test. Based on the results of the analysis of funding decisions and dividend policy simultaneously and significantly affect the value of the company, partially funding decisions and dividend policy each affect the value of the company.